Родина Cleomaceae у флорі України - Ільїнська, А.П. (Український ботанічний журнал, 2014)
Для флоры Украины приведены два рода (Cleome L. s. str.
и Tarenaya Raf.) и три вида (С. canescens Steven ex DC.,
С. donetzica Tzvelev и T. hassleriana (Chodat) Iltis) семейства
Cleomaceae Bercht. et J. Presl. Представлены номенклатура,
описания, распространение, местонахождения, некоторые
особенности биологии, а так же ключи для определения изученных родов и видов. Two genus (Cleome L. s. str. and Tarenaya Raf.) and three
species (С. canescens Steven ex DC., С. donetzica Tzvelev
and T. hassleriana (Chodat) Iltis) from the
family Cleomaceae Bercht. et J. Presl for the flora of Ukraine are
resulted. The nomenclature, descriptions, geography, locations,
some data about biology and key to identification of the genus et
species are provided.